PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAN KONSEP SISWA - Selvi Fajaryani; Anni Malihatul Hawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the lack of students' conceptual understanding ability. This study aims to determine the Effect of the Problem Based Learning (PBL) Learning Model assisted by the Reading Diorama Room Media (BIDIBA) on Students' Concept Understanding Ability. This type of research uses a quantitative approach with a Quasi-experimental design in the form of the nonequivalent control group design. The sampling technique in this study uses a purposive sampling method with a purposive sampling technique. The sample of this study was class III A and B of Sidomulyo 04 Public Elementary School. Data collection techniques in this study are test techniques (pre-test and post-test) and non-test (observation, questionnaires, structured interviews, and documentation). The data analysis techniques are normality test, homogeneity test, independent sample t test, and simple linear regression test. The results of the study show that: (1) There is a difference in the use of the Problem Based Learning (PBL) model assisted by the Bilik Diorama Baca (BIDIBA) media on students' conceptual understanding abilities, this can be proven by the results of the independent test until the t test with a significance value of 0.002 <0.05 Ho is rejected and Ha is accepted; and (2) There is an influence of the use of the Problem Based Learning (PBL) model assisted by the Bilik Diorama Baca (BIDIBA) media on students' conceptual understanding abilities, this can be proven by the results of the linear regression test with a significance value of 0.008 <0.05 Ho is rejected and Ha is accepted. The results of this study can be concluded that the use of the Problem Based Learning (PBL) model assisted by the Bilik Diorama Baca (BIDIBA) media has an effect on students' conceptual understanding abilities in grade III. Keywords : Problem Based Learning (PBL); Bilik Diorama Baca (BIDIBA); Conseptual Understanding